Factors that influence saving behaviour among households in Malaysia / Muhammad Afiq Alias and Nurfazliena Syaiha Mustaffa - Alias, Muhammad Afiq; Mustaffa, Nurfazliena Syaiha (Faculty of Business and Management, 2016)
Malaysia has experienced oscillating in saving funds rate over the few years. These situations became a worrying by analyst, educator, manufacturer and household also more worried about their future. Therefore, the purpose of this study is to investigate the factors that influence saving behaviour among Malaysian household. Interest Rate (IR), Inflation Rate (IFR), Consumption Level (CL) and Income Level (IL) are variables that were taken into this research with Saving Behaviour (SBAH). This study is based on the time series data collections which encompass 30 years in yearly basis. The period starting from 1984 to 2014. The researcher is using Eviews 9 software to generate all the data and analyse it for further investigation. After the data generated, the result obtained shows that only one out of four variables accepted which is inflation rate (IFR) are significantly related to the influence of saving behaviour. While the other three variables Interest Rate (IR), Consumption Level (CL) and Income Level (IL) are rejected. The overall investigation is to emphasize the awareness of saving behaviour among household towards the changes of economic situations factors and help household in Malaysia to have a proper financial management especially in saving.